Individual differences in short-term social dynamics: theoretical perspective and empirical development of the social dynamics scale - Wrzus, Cornelia; Roos, Yannick; Krämer, Michael D.; Richter, David (Current psychology, 2024)
People have a need to form and maintain fulfilling social contact, yet they differ with respect to with whom they satisfy the need and how quickly this need is deprived or overly satiated. These social dynamics across relationships and across time are theoretically delineated in the current article. Furthermore, we developed a questionnaire to measure individual differences in three aspects of such social dynamics: (a) Family-friends interdependence, (b) Social deprivation, and (c) Social oversatiation. In a longitudinal study spanning 9 weeks in spring 2020, in total 471 participants (18-75 years, 47% women) answered the newly developed items on social dynamics, questionnaires on social dispositions (e.g., affiliation motive, need to be alone, social anxiety), and questions on personal and indirect contact with family and friends during nationwide contact restrictions related to COVID-19. The results showed that individual differences in Family-friends interdependence, Social deprivation, and Social oversatiation can be measured reliably, validly, and with predictive value for changes in daily contact as contact restrictions were loosened. We discuss potential applications of the Social Dynamics Scale (SDS) for studying social relationships in healthy and clinical populations, and conclude that the brief self-report questionnaire of social dynamics can be useful for situations and samples where direct behavioral observations are not feasible.